Austrolebias univentripinnis sp. nov. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the Mirim Lagoon basin, southern Brazil - Costa, Wilson J.e.m.; Cheffe, Morevy M. (Zootaxa, 2005)
Austrolebias univentripinnis n. sp. is described from the Jaguarão River floodplains, Mirim Lagoon basin, southern Brazil. It is a member of a clade that also includes A. viarius, A. arachan, A. adloffi, A. charrua, A. minuano, A. nigrofasciatus, A. vandenbergi, A. bellottii, and A. melanoorus, which is diagnosed by the possession of a long and triangular anal fin in females. The new species is similar to A. bellottii and A. melanoorus in having the urogenital papilla completely attached to the anal fin in males; it differs from A. bellottii in having the dorsal fin more anteriorly placed in males, a shorter anal-fin base, lesser body depth, and wider basihyal; it is distinguished from A. melanoorus by the number of rostral neuromasts, degree of pelvic-fin fusion, morphology of dorsum in females, color pattern of unpaired fins in males, and color pattern of flank in both sexes.